Present and Future of Endoscopic Ultrasound-Guided Tissue Acquisition in Solid Pancreatic Tumors - Jae Keun Park; Kwang Hyuck Lee (Korean Society of Gastrointestinal Endoscopy, 2019)
Endoscopic ultrasound-guided tissue acquisition (EUS-TA) is a well-established method for pathological diagnosis of solid pancreatic neoplasm. It can be performed either as EUS-guided fine-needle aspiration (EUS-FNA) or EUS-guided fine-needle biopsy (EUSFNB). The incidence of adverse events related to EUS-TA is less than 1%. The factors that affect the diagnostic accuracy and specimen adequacy include the techniques used, type and size of the needle, competency of endosonographers, presence of cytopathologists/ cytotechnologists, and rapid on-site examination. EUS-TA may contribute to precision medicine through obtaining tissue samples for next-generation sequencing. T﻿he current status, several clinical issues for diagnostic yield and adverse events, and future perspectives of EUS-FNA/FNB for diagnosing pancreatic neoplasm have been discussed in this review article.